Passive transfer of immunity in water buffalo calves and its effect before weaning. - Cáseres-Álvarez, Beatriz; Elizondo-Salazar, Jorge Alberto (Agronomía Mesoamericana, 2013)
The objective of this study was to characterize the immune status of water buffalo calves in a commercial buffalo farm in the Northern Huetar region of Costa Rica. The data presented is for total serum protein measurements obtained between August 2010 and February 2011 in the province of Alajuela, Costa Rica. In that period of time, the farm was visited weekly and blood samples were taken by jugular venipuncture from 116 buffalo calves (60 females and 56 males) between 1 and 7 days of age. For the purpose of this study, failure of passive immunity was considered when TSP was less than 5.5 g/dl. TSP concentration ranged from 4.2 and 9.8 g/dl, with an overall mean of 6.9 g/dl. Of all the animals evaluated, 12.9% had failure of passive transfer of immunity. When considering sex of the calves, 11.7% of females and 14.2% of males failed to obtain adequate levels of immunity, but TSP concentration showed no significant differences between female and male calves (6.9 vs. 6,8 g/dl, respectively). Buffalo male calves that had an adequate passive transfer achieved greater live weight during the second and third months of age with respect to those males which showed a failure of passive transfer of immunity.